Electronic Identification System of Hazardous Volatile Organic Compound Gases using Roselle-Chitosan Blend - Ahmed M.S. Eljali; Irwana Nainggolan; Tulus Ikhsan Nasution; Shahrir Hashim (IAES Indonesia Section, 2015)
This paper presents a study on design and fabrication of an electronic identification system (EIS) for some volatile organic compounds i.e. toluene, ethanol and methanol through vaporization technology. A new sensing material of roselle-chitosan blending thin film based on electrochemical deposition method was used to guarantee the differentiation and the accuracy of the identification system. Chitosan smart gel with 2% acetic acid was prepared and then roselle extract was blended to enhance the sensing properties of the chitosan film. Differentiation ability was studied by exposing 50ppm of toluene, ethanol and methanol vapor to the sensing material. The accuracy of the identification system was tested by IV electrical testing. The analyzed data demonstrated that the electronic identification system is capable of identifying different volatile organic compound gases at room temperature successfully. The roselle-chitosan film sensors showed the characteristic of a reliable sensor i.e. good sensitivity, selectivity, repeatability, recovery and stable.